Clinical Outcome in Newborns after Omission of Heart Rate Counting Step vs Standard Neonatal Resuscitation: A Randomised Controlled Trial - Yashwant Kumar Rao; Shinka Gond; Pratibha Singh; Tanu Midha; Neha Agarwal (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: In all Neonatal Resuscitation Program (NRP) scenarios, Heart Rate (HR) counting is essential to assess the response to resuscitation. Undue delay in initiating Positive Pressure Ventilation (PPV) due to the time taken in HR counting may increase the risk of hypoxic injury and infant mortality. Aim: To observe whether omitting the HR counting step in the First Golden Minute (FGM) and early initiation of PPV affects outcomes. Materials and Methods: The present Randomised Controlled Trial (RCT) was conducted in the Special Newborn Care Unit (SNCU), GSVM Medical College, Kanpur, Uttar Pradesh, India, from September 2020 to March 2022. A total of 67 newborns were included, with 34 in the control group (group 1) and 33 in the intervention group (group 2). In the control group, neonatal resuscitation was performed according to Facility-based Newborn Care (FBNC) guidelines, while in the intervention group, only the HR counting step was omitted from the FGM. Both groups of newborns were assessed for outcomes including normal baby, baby developing Hypoxic Ischaemic Encephalopathy (HIE) stage I, II and III, and death. Data was compiled and analysed using percentages for categorical variables. Continuous variables were analysed using mean and standard deviation of Z score and Student's t-test. A p-value less than 0.05 was considered statistically significant. Results: The mean gestational age was 38.3±5.8 weeks in group 1 and 37.9±6.1 weeks in group 2. Gender distribution was almost equal, with 19 (56%) female newborns in group 1 and 17 (52%) female newborns in group 2. The mean total time from birth to the end of PPV (in seconds) was significantly lower in group 2 (63.47±7.09) compared to group 1 (78.18±8.36), with a p-value of <0.001. Clinical outcomes in group 1 included 10 (29.41%) normal babies, 12 (35.29%) with HIE-I, 5 (14.71%) with HIE-II, 5 (14.7%) with HIE-III, and 2 (5.88%) deaths. In group 2, the outcomes were 14 (42.42%) normal babies, 6 (18.18%) with HIE-I, 8 (24.24%) with HIE-II, 4 (12.12%) with HIE-III, and 1 (3.03%) death. Conclusion: The present study demonstrated that even after omitting the HR counting step from the FGM, the outcomes in terms of HIE and death are similar to those observed after following the standard NRP protocol.